RETRACTED: PUBLIC-PRIVATE PARTNERSHIP: EVOLUTION OF DEVELOPMENT AND POPULARITY OF COVERAGE IN SCIENTIFIC PUBLICATIONS - Tarabanovskyi, Petro; Hrytsenko, Larysa; Samoilikova, Anastasiia; Buła, Piotr (Socio-economic relations in the digital society, 2024)
RETRACTION NOTICEThe Editorial Board of the Publication "SOCIO-ECONOMIC RELATIONS IN THE DIGITAL SOCIETY", has decided to retract the article by Tarabanovskyi, P., Hrytsenko, L., Samoilikova, A., & Buła, P. (2024). PUBLIC-PRIVATE PARTNERSHIP: EVOLUTION OF DEVELOPMENT AND POPULARITY OF COVERAGE IN SCIENTIFIC PUBLICATIONS., published in the Vol. 1 No. 51, pp. 5-20. (https://doi.org/10.55643/ser.1.51.2024.559).The reason for retraction is a breach of the Publishing Ethics of the Publication due to the presence of a significant amount of copied material from the article by Azarian, M.; Shiferaw, A.T.; Stevik, T.K.; Lædre, O.; Wondimu, P.A. Public-Private Partnership: A Bibliometric Analysis and Historical Evolution. Buildings 2023, 13, 2035. https://doi.org/10.3390/buildings13082035.The article was retracted on 02/07/2024
Keywords: public-private partnership; business educational models; public services; education; economic and social infrastructure; motivation; agricultural production